High-capacity and high-stability resin-based hard carbon negative electrode material and preparation method thereof

CN122930869APending Publication Date: 2026-10-16HUIYANG (GUIZHOU) NEW ENERGY MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611098730.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-23
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

例如,部分技术通过添加单一模板剂构建孔结构,虽能提升比表面积和离子传输速率,但过度造孔会降低材料振实密度,导致体积能量密度下降;部分技术采用单一异质原子掺杂,虽能增加储钠活性位点,但掺杂均匀性难以控制,易引入不可逆反应位点,进一步降低首次库伦效率;还有技术通过表面包覆改善界面稳定性,但会增加制备步骤,且可能阻碍离子传输,影响倍率性能

Benefits of technology

1.本发明采用木质素接枝改性树脂前驱体,不仅能提高树脂的残碳率,其分子结构中的羟基、羧基等官能团还能与树脂形成稳定的交联网络,有效抑制碳化过程中硬碳材料的结构坍塌;同时,木质素中的芳香环结构能促进石墨化程度的均匀性,优化储钠位点,解决了传统树脂基硬碳结构松散、储钠位点不足的问题,经测试,本发明制备的硬碳材料振实密度提升至0.8-1.0 。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 3C0SBEOPPY90HRZ568M3B5T9MOACHMPKYNJD1VQ5
    Figure 3C0SBEOPPY90HRZ568M3B5T9MOACHMPKYNJD1VQ5
  • Figure 8YNFT7PZ5YKGD8AQIRLT6X6JWD4V23EJZBCL8L3O
    Figure 8YNFT7PZ5YKGD8AQIRLT6X6JWD4V23EJZBCL8L3O
  • Figure DNGDM7ONL29QHFVUVNEWSV8HGVX571U8FPP0PTHZ
    Figure DNGDM7ONL29QHFVUVNEWSV8HGVX571U8FPP0PTHZ
Patent Text Reader

Abstract

The application relates to the technical field of sodium ion battery negative electrode materials, in particular to a resin-based hard carbon negative electrode material with high capacity and high stability and a preparation method thereof. The resin-based hard carbon negative electrode material is prepared from a resin precursor modified by lignin grafting, an MgO-ZnO composite pore adjusting agent, a nitrogen-phosphorus-sulfur heteroatomic dopant, a dispersant and deionized water through steps of modification, mixing and carbonization, and solves the defects of low tap density and poor first coulomb efficiency caused by single template pore forming. Through testing, the tap density of the hard carbon material prepared by the application is improved to 0.8-1.0, and the first coulomb efficiency reaches more than 88%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of sodium-ion battery anode material technology, specifically to a high-capacity, high-stability resin-based hard carbon anode material and its preparation method. Background Technology

[0002] Sodium-ion batteries, due to their abundant resources, low cost, and high safety, have broad application prospects in large-scale energy storage, low-speed electric vehicles, and portable electronic devices. The key to improving their performance lies in breakthroughs in anode materials. Hard carbon materials, with their suitable interlayer spacing, high sodium storage capacity, and good cycle stability, are currently one of the most promising anode materials for sodium-ion batteries for industrialization.

[0003] Resin-based organic polymers such as phenolic resin, epoxy resin, and furfural resin have advantages such as high carbon residue, easy structural control, low raw material cost, and great industrialization potential, making them preferred precursors for preparing hard carbon anode materials. However, existing resin-based hard carbon anode materials still face three major technical bottlenecks in practical applications: First, limited specific capacity. The reversible specific capacity of conventional resin-based hard carbon is usually only 200-350 mAh / g, far lower than theoretical expectations, making it difficult to meet the needs of high-energy-density sodium-ion batteries. Second, low initial coulombic efficiency, usually only 70-85%, with severe sodium loss leading to a decrease in overall battery energy utilization. Third, insufficient cycle stability and rate performance. Hard carbon materials formed by direct carbonization of resin have problems such as unreasonable pore structure, uneven graphitization, and high interfacial impedance. During long-term charge and discharge, structural collapse and SEI film rupture are prone to occur, leading to rapid capacity decay and failing to meet the long-cycle requirements of large-scale energy storage.

[0004] To address these issues, various improvement schemes have been proposed in existing technologies, such as single-channel modification, heteroatom doping, or surface coating. For example, some technologies construct pore structures by adding a single template agent, which can improve specific surface area and ion transport rate, but excessive pore formation can reduce the material's tap density, leading to a decrease in volumetric energy density. Some technologies use single heteroatom doping, which can increase sodium storage active sites, but doping uniformity is difficult to control, easily introducing irreversible reaction sites and further reducing the first coulombic efficiency. Other technologies improve interfacial stability through surface coating, but this increases the preparation steps and may hinder ion transport, affecting rate performance. In addition, existing resin-based hard carbon preparation processes often suffer from cumbersome steps, difficulty in controlling process parameters, and high industrialization challenges, failing to achieve a balance between performance and cost.

[0005] Therefore, in view of the shortcomings of the existing technology, developing a resin-based hard carbon anode material that has high specific capacity, high initial coulombic efficiency, excellent cycle stability and rate performance, and is simple to prepare, cost controllable and suitable for large-scale production has become an urgent technical problem to be solved in the field of sodium-ion batteries. Summary of the Invention

[0006] To address the aforementioned deficiencies in existing technologies, the present invention aims to provide a high-capacity, high-stability resin-based hard carbon anode material and its preparation method. By synergistically regulating resin precursor modification, pore structure design, and heteroatom doping, the sodium storage performance of the hard carbon material is comprehensively improved. At the same time, the preparation process is simplified, production costs are reduced, and the high-performance requirements of large-scale energy storage and new energy vehicles for sodium-ion battery anode materials are met.

[0007] One objective of this invention is to provide a resin-based hard carbon anode material prepared by the aforementioned method, which is prepared from the following raw materials in parts by weight: 60-80 parts of modified resin precursor, 5-15 parts of composite pore regulator, 3-8 parts of heteroatomic dopant, 1-3 parts of dispersant, and 20-40 parts of deionized water; wherein the modified resin precursor is a resin modified by lignin grafting; and the composite pore regulator is a compound system of MgO-ZnO composite template agent and non-carbon-forming polymer.

[0008] Further, the dispersant is polyvinylpyrrolidone (PVP) or sodium carboxymethyl cellulose (CMC); the lignin is alkali lignin; the resin is phenolic resin or epoxy resin; the non-carbon-forming polymer is polystyrene; the mass ratio of the MgO-ZnO composite template agent to polystyrene is 2-4:1; and the heteroatomic dopant is a nitrogen-phosphorus-sulfur composite dopant.

[0009] Furthermore, the particle size of the MgO-ZnO composite template agent is 50-100 nm, the number average molecular weight of the polystyrene is 50,000-100,000 g / mol, the molecular weight of the alkali lignin is 5,000-10,000 g / mol, and the MgO-ZnO composite template agent has a MgO-ZnO mass ratio of 3-5:1; the nitrogen-phosphorus-sulfur composite dopant is composed of urea, ammonium dihydrogen phosphate, and thiourea mixed in a mass ratio of 4-6:2-3:1.

[0010] The method for preparing the lignin-grafted modified phenolic resin or epoxy resin is as follows: phenolic resin or epoxy resin and lignin are mixed at a mass ratio of 8-10:1, and 2-3% of an alkaline catalyst (sodium hydroxide or potassium hydroxide) is added. The mixture is stirred and reacted at 60-100℃ for 2-6 hours, cooled to room temperature, washed with deionized water until neutral, dried at 80-110℃ for 4-8 hours, and ground through a 100-mesh sieve to obtain the modified resin precursor. The lignin is alkali lignin with a molecular weight of 5000-10000 g / mol.

[0011] The phenolic resin used is novolac type phenolic resin with a softening point of 80-100℃, and the epoxy resin used is E-51 type to ensure the smooth progress of the grafting reaction.

[0012] The weight part can be g, kg, t, etc., and preferably one weight part is 10g.

[0013] The physicochemical parameters of the resin-based hard carbon anode material are: tap density 0.8-1.2. Specific surface area 5-25 The average pore size is 2-5 nm, the graphite interlayer spacing is 0.38-0.40 nm, and the total amount of nitrogen, phosphorus and sulfur doping is 3-6 at.%; among which, the nitrogen doping amount is 1.5-3 at.%, the phosphorus doping amount is 1-2 at.%, and the sulfur doping amount is 0.5-1 at.%.

[0014] Another object of the present invention is to provide a method for preparing a high-capacity, high-stability resin-based hard carbon anode material, comprising the following steps: S1. Preparation of modified resin precursor: Mix resin and lignin at a mass ratio of 8-10:1, add 2-3% alkaline catalyst of total mass, stir at 60-100℃ for 2-6h, cool to room temperature after reaction, wash with deionized water until neutral, dry at 80-110℃ for 4-8h, grind through 100 mesh sieve to obtain modified resin precursor; S2. Preparation of mixed slurry: Mix 60-80 parts of modified resin precursor, 5-15 parts of composite channel conditioner, 3-8 parts of heteroatomic dopant, and 1-3 parts of dispersant, add 20-40 parts of deionized water, and stir in a high-speed stirrer at a speed of 1000-1500 r / min for 30-60 min to obtain a uniform mixed slurry. S3. Pre-oxidation treatment: Place the mixed slurry in a vacuum drying oven and dry it at 60-80℃ for 12-24 hours; after drying, crush the material in a pulverizer, pass it through a 100-mesh sieve, and place it in a tube furnace. Under an oxygen-containing atmosphere, heat it to 250-300℃ at a heating rate of 2-5℃ / min and hold it at that temperature for 3-5 hours to complete the pre-oxidation treatment, so that the resin precursor crosslinks and cures, while removing some volatile impurities.

[0015] S4. Pre-carbonization treatment: The pre-oxidized material is transferred to a tube furnace in an argon inert atmosphere and heated to 500-700℃ at a heating rate of 3-8℃ / min. The temperature is held for 2-4 hours to carry out pre-carbonization, remove the volatile components in the composite pore conditioning agent, and initially form a pore structure and a uniform distribution of doped atoms.

[0016] S5. Activation and High-Temperature Carbonization: Transfer the pre-carbonized material and continue heating it to 800-950℃ at a rate of 5-8℃ / min under an inert argon atmosphere. gas, the At a flow rate of 20-60 mL / min, the temperature is maintained for 1-4 h to activate and regulate the pore structure. After the temperature is maintained, the temperature is raised to 1300-1600℃ at the same rate and maintained for 6-10 h to complete the high-temperature carbonization. S6. Pickling and impurity removal: Cool the high-temperature carbonized material to room temperature, soak it in dilute hydrochloric acid with a concentration of 1-2 mol / L for 2-4 hours, and stir continuously at a speed of 200-500 r / min to remove the residual metal oxides of the composite template agent. Then wash it with deionized water until neutral and dry it at 80-110℃ for 4-6 hours.

[0017] S7. Coating and carbonization: The acid-washed and impurity-removed material is mixed evenly with 5-10% by mass of asphalt, transferred to a tube furnace, and heated to 900-1100℃ at a heating rate of 5-8℃ / min under an argon inert atmosphere. The temperature is held for 3-6 hours. After the holding period, the material is cooled with the furnace and passed through a 325-mesh sieve to obtain the resin-based hard carbon anode material.

[0018] Further, in step S3, the oxygen-containing atmosphere is a mixture of oxygen and nitrogen, wherein the oxygen volume fraction is 20-30%, and the atmosphere flow rate is 50-80 mL / min; in steps S4 and S5, the inert atmosphere flow rate is 50-100 mL / min.

[0019] Furthermore, in step S5, The gas flow rate is 30-50 mL / min; in step S6, the dilute hydrochloric acid soaking process is continuously stirred at a stirring rate of 300-500 r / min.

[0020] Furthermore, in step S7, the asphalt is coal tar pitch, with the following core indicators: softening point 250±5℃, coking value 75-78%, quinoline insolubles 18-26%, toluene insolubles 54-58%, ash content ≤0.3%, and it is a black solid at room temperature.

[0021] Another objective of this invention is to provide an application of the resin-based hard carbon anode material prepared by the aforementioned method. The hard carbon anode material is mixed with a conductive agent and a binder at a mass ratio of 80-85:10-15:5, and N-methylpyrrolidone (NMP) is added until the slurry solid content reaches 45%. After stirring evenly, the mixture is coated onto copper foil, dried, and rolled to serve as the anode of a sodium-ion battery. It is then assembled with a positive electrode, electrolyte, and separator to form a sodium-ion battery.

[0022] Furthermore, the conductive agent is acetylene black, the binder is polyvinylidene fluoride, and the hard carbon negative electrode material is mixed with acetylene black and polyvinylidene fluoride at a mass ratio of 80-85:10-15:5.

[0023] The beneficial effects of this invention are: 1. This invention utilizes lignin-grafted modified resin precursors, which not only improve the resin's residual carbon content but also allow the hydroxyl and carboxyl functional groups in the lignin's molecular structure to form a stable cross-linking network with the resin, effectively inhibiting structural collapse of hard carbon materials during carbonization. Simultaneously, the aromatic ring structure in lignin promotes the uniformity of graphitization and optimizes sodium storage sites, solving the problems of loose structure and insufficient sodium storage sites in traditional resin-based hard carbon materials. Testing shows that the tap density of the hard carbon material prepared by this invention is increased to 0.8-1.0. .

[0024] 2. This invention employs nitrogen-phosphorus-sulfur composite doping. The introduction of nitrogen atoms can form pyridine nitrogen and graphitic nitrogen, enhancing the sodium ion adsorption capacity; phosphorus atoms can be doped into the carbon framework, expanding the interlayer spacing of graphite and reducing the sodium ion intercalation energy barrier; sulfur atoms can form CSC bonds, introducing pseudocapacitive contributions. The synergistic effect of these three factors increases the reversible specific capacity of hard carbon materials to 360-410 mAh / g. At the same time, composite doping can improve the conductivity of the material, reduce the interfacial impedance, and improve rate performance and cycle stability.

[0025] 3. The resin-based hard carbon anode material prepared by this invention, when applied to sodium-ion batteries, exhibits a reversible specific capacity of up to 403.4 mAh / g at a current density of 0.1 A / g, with an initial coulombic efficiency of over 88%. At a current density of 1 A / g, the capacity retention rate after 1000 cycles can reach up to 92.4%. Its comprehensive performance is superior to existing resin-based hard carbon anode materials, and it can be widely used in sodium-ion batteries for large-scale energy storage, new energy vehicles, portable electronic devices, and other fields. Attached Figure Description

[0026] Figure 1 The images are scanning electron microscope (SEM) images of the resin-based hard carbon anode materials prepared in Examples 1 and 2 of this invention. Detailed Implementation

[0027] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments. The illustrative embodiments and descriptions of the present invention are used to explain the present invention, but are not intended to limit the present invention.

[0028] Unless otherwise specified, the experimental methods used in the following examples are conventional methods; unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0029] Example 1

[0030] A high-capacity, high-stability resin-based hard carbon anode material is prepared from the following raw materials in parts by weight: 70 parts modified phenolic resin, 10 parts composite pore conditioner, 5 parts nitrogen-phosphorus-sulfur composite dopant, 2 parts PVP dispersant, and 30 parts deionized water.

[0031] The modified phenolic resin is prepared by mixing novolac type phenolic resin and lignin with a molecular weight of 8000 g / mol at a mass ratio of 9:1, adding sodium hydroxide accounting for 3% of the total mass, stirring and reacting at 90°C for 4 hours, cooling to room temperature, washing with deionized water until neutral, drying at 90°C for 6 hours, and grinding through a 100-mesh sieve to obtain modified phenolic resin powder. The composite pore regulator is a compound system of MgO-ZnO composite template agent and polystyrene, with a mass ratio of 3:1; the MgO-ZnO composite template agent has a mass ratio of 4:1, a particle size of 80nm, and a polystyrene number-average molecular weight of 80000g / mol.

[0032] The nitrogen-phosphorus-sulfur composite dopant is composed of urea, ammonium dihydrogen phosphate, and thiourea mixed in a mass ratio of 5:2.5:1.

[0033] The preparation method is as follows: S1. Preparation of modified phenolic resin precursor: Prepare modified phenolic resin powder according to the above method for later use; S2. Preparation of mixed slurry: Mix 70 parts of modified phenolic resin, 10 parts of composite pore conditioner, 5 parts of nitrogen-phosphorus-sulfur composite dopant, and 2 parts of PVP dispersant, add 30 parts of deionized water, and stir in a high-speed stirrer at a speed of 1200 r / min for 45 min to obtain a uniform mixed slurry. S3. Pre-oxidation treatment: The mixed slurry is placed in a vacuum drying oven and dried at 70℃ for 18h; the dried material is crushed by a pulverizer, passed through a 100-mesh sieve, and placed in a tube furnace. Under an oxygen-containing atmosphere with an oxygen volume fraction of 25% and an oxygen-containing atmosphere flow rate of 60mL / min, the temperature is raised to 280℃ at a heating rate of 3℃ / min and held for 4h to complete the pre-oxidation. S4. Pre-carbonization treatment: The pre-oxidized material is transferred to a tube furnace in an argon inert atmosphere and heated to 600°C at a heating rate of 5°C / min. The temperature is held for 3 hours to complete the pre-carbonization. S5. Activation and High-Temperature Carbonization: Transfer the pre-carbonized material and continue heating to 850°C at 6°C / min under an argon atmosphere, then introduce the material at a flow rate of 40 mL / min. Gas, heat-activated for 2 hours; after heat-activated, heat up to 1450℃ at the same rate and heat for 8 hours to complete high-temperature carbonization. S6. Pickling and impurity removal: Cool the high-temperature carbonized material to room temperature, soak it in 1.5mol / L dilute hydrochloric acid for 3 hours with continuous stirring at 350r / min to remove the residual metal oxides of the composite template agent, then wash it with deionized water until neutral, and dry it at 95℃ for 5 hours.

[0034] S7. Coating and carbonization: The acid-washed and impurity-removed material is mixed evenly with 8% by mass of asphalt, transferred to a tube furnace, and heated to 1000℃ at a heating rate of 6℃ / min under an argon atmosphere and held for 4 hours. After the holding period, the carbonized material is cooled with the furnace and passed through a 325-mesh sieve to obtain resin-based hard carbon anode material.

[0035] Example 2

[0036] A high-capacity, high-stability resin-based hard carbon anode material is prepared from the following raw materials in parts by weight: 65 parts modified epoxy resin, 8 parts composite pore conditioner, 4 parts nitrogen-phosphorus-sulfur composite dopant, 1.5 parts CMC dispersant, mixed with 25 parts deionized water.

[0037] The modified epoxy resin is prepared by mixing E-51 type epoxy resin and lignin with a molecular weight of 6000 g / mol at a mass ratio of 8:1, adding sodium hydroxide accounting for 2% of the total mass, stirring and reacting at 85°C for 2 hours, cooling to room temperature, washing with deionized water until neutral, drying at 80°C for 4 hours, and grinding through a 100-mesh sieve to obtain modified epoxy resin powder. The composite pore regulator is a compound system of MgO-ZnO composite template agent and polystyrene, with a mass ratio of 2:1; the mass ratio of MgO-ZnO is 3:1, the particle size is 60nm, and the number average molecular weight of polystyrene is 60000 g / mol.

[0038] The nitrogen-phosphorus-sulfur composite dopant is composed of urea, ammonium dihydrogen phosphate, and thiourea mixed in a mass ratio of 4:2:1.

[0039] The preparation method is as follows: S1. Preparation of modified phenolic resin precursor: Prepare modified phenolic resin powder according to the above method for later use; S2. Preparation of mixed slurry: Mix 65 parts of modified phenolic resin, 8 parts of composite pore conditioner, 4 parts of nitrogen-phosphorus-sulfur composite dopant, and 1.5 parts of PVP dispersant, add 25 parts of deionized water, and stir in a high-speed stirrer at 1100 r / min for 30 min to obtain a uniform mixed slurry. S3. Pre-oxidation treatment: Place the mixed slurry in a vacuum drying oven and dry it at 65℃ for 24 hours; after drying, crush the material in a pulverizer, pass it through a 100-mesh sieve, and place it in a tube furnace. Under an oxygen-containing atmosphere with an oxygen volume fraction of 20% and an oxygen-containing atmosphere flow rate of 50 mL / min, heat it to 260℃ at a heating rate of 2℃ / min and hold it at that temperature for 3 hours to complete the pre-oxidation. S4. Pre-carbonization treatment: The pre-oxidized material is transferred to a tube furnace in an argon inert atmosphere and heated to 500°C at a heating rate of 5°C / min. The temperature is held for 2 hours to complete the pre-carbonization. S5. Activation and High-Temperature Carbonization: Transfer the pre-carbonized material and continue heating to 800°C at 5°C / min under an argon atmosphere, then introduce the material at a flow rate of 20 mL / min. Gas, heat-activated for 1 hour; after heat-activation, heat up to 1300℃ at the same rate and heat for 6 hours to complete high-temperature carbonization. S6. Pickling to remove impurities: Cool the high-temperature carbonized material to room temperature, soak it in 1mol / L dilute hydrochloric acid for 2 hours with continuous stirring at 200r / min to remove residual metal oxides of the composite template agent, then wash it with deionized water until neutral, and dry it at 80℃ for 4 hours.

[0040] S7. Coating and carbonization: The acid-washed and impurity-removed material is mixed evenly with 5% by mass of asphalt, transferred to a tube furnace, and heated to 900℃ at a heating rate of 5℃ / min under an argon atmosphere. The temperature is held for 3 hours. After the holding period, the material is cooled with the furnace and passed through a 325-mesh sieve to obtain the resin-based hard carbon anode material.

[0041] Example 3

[0042] A high-capacity, high-stability resin-based hard carbon anode material is prepared from the following raw materials in parts by weight: 75 parts modified epoxy resin, 12 parts composite pore conditioner, 7 parts nitrogen-phosphorus-sulfur composite dopant, 1.5 parts PVP dispersant, and 35 parts deionized water.

[0043] The modified epoxy resin is prepared by mixing novolac phenolic resin and lignin with a molecular weight of 10000 g / mol at a mass ratio of 10:1, adding sodium hydroxide accounting for 2.5% of the total mass, stirring and reacting at 100℃ for 6 hours, cooling to room temperature, washing with deionized water until neutral, drying at 110℃ for 8 hours, and grinding through a 100-mesh sieve to obtain modified epoxy resin powder. The composite pore regulator is a compound system of MgO-ZnO composite template agent and polystyrene, with a mass ratio of 4:1; the mass ratio of MgO-ZnO is 5:1, the particle size is 90nm, and the number average molecular weight of polystyrene is 90000 g / mol.

[0044] The nitrogen-phosphorus-sulfur composite dopant is composed of urea, ammonium dihydrogen phosphate, and thiourea mixed in a mass ratio of 6:3:1.

[0045] The preparation method is as follows: S1. Preparation of modified phenolic resin precursor: Prepare modified phenolic resin powder according to the above method for later use; S2. Preparation of mixed slurry: Mix 75 parts of modified phenolic resin, 12 parts of composite pore conditioner, 7 parts of nitrogen-phosphorus-sulfur composite dopant, and 3 parts of PVP dispersant, add 35 parts of deionized water, and stir in a high-speed stirrer at a speed of 1500 r / min for 60 min to obtain a uniform mixed slurry. S3. Pre-oxidation treatment: Place the mixed slurry in a vacuum drying oven and dry it at 80℃ for 12 hours; after drying, crush the material in a pulverizer, pass it through a 100-mesh sieve, and place it in a tube furnace. Under an oxygen-containing atmosphere with an oxygen volume fraction of 20% and an oxygen-containing atmosphere flow rate of 80 mL / min, heat it to 300℃ at a heating rate of 5℃ / min and hold it at that temperature for 5 hours to complete the pre-oxidation. S4. Pre-carbonization treatment: The pre-oxidized material is transferred to a tube furnace in an argon inert atmosphere and heated to 700°C at a heating rate of 8°C / min. The temperature is held for 3 hours to complete the pre-carbonization. S5. Activation and High-Temperature Carbonization: Transfer the pre-carbonized material and continue heating to 950°C at 8°C / min under an argon atmosphere, then introduce the material at a flow rate of 60 mL / min. Gas, heat-activated for 4 hours; after heat-activated, heat up to 1600℃ at the same rate and heat for 10 hours to complete high-temperature carbonization. S6. Pickling and impurity removal: Cool the high-temperature carbonized material to room temperature, soak it in 2mol / L dilute hydrochloric acid for 4 hours with continuous stirring at 500r / min to remove residual metal oxides of the composite template agent, then wash it with deionized water until neutral, and dry it at 110℃ for 6 hours.

[0046] S7. Coating and carbonization: The acid-washed and impurity-removed material is mixed evenly with 10% by mass of asphalt, transferred to a tube furnace, and heated to 1100℃ at a heating rate of 8℃ / min under an argon atmosphere and held for 6 hours. After the holding period, the carbonized material is cooled with the furnace and passed through a 325-mesh sieve to obtain the resin-based hard carbon anode material.

[0047] Example 4

[0048] A high-capacity, high-stability resin-based hard carbon anode material is prepared from the following raw materials in parts by weight: 60 parts modified epoxy resin, 5 parts composite pore conditioner, 8 parts nitrogen-phosphorus-sulfur composite dopant, 1 part CMC dispersant, and 20 parts deionized water.

[0049] The modified epoxy resin is prepared by mixing E-51 type epoxy resin and lignin with a molecular weight of 10000 g / mol at a mass ratio of 9:1, adding sodium hydroxide accounting for 2.5% of the total mass, stirring and reacting at 90°C for 5 hours, cooling to room temperature, washing with deionized water until neutral, drying at 100°C for 5 hours, and grinding through a 100-mesh sieve to obtain modified epoxy resin powder. The composite pore regulator is a compound system of MgO-ZnO composite template agent and polystyrene, with a mass ratio of 3:1; the mass ratio of MgO-ZnO is 4:1, the particle size is 80nm, and the number average molecular weight of polystyrene is 90000g / mol.

[0050] The nitrogen-phosphorus-sulfur composite dopant is composed of urea, ammonium dihydrogen phosphate, and thiourea mixed in a mass ratio of 5:3:1.

[0051] The preparation method is as follows: S1. Preparation of modified phenolic resin precursor: Prepare modified phenolic resin powder according to the above method for later use; S2. Preparation of mixed slurry: Mix 60 parts of modified phenolic resin, 5 parts of composite pore conditioner, 8 parts of nitrogen-phosphorus-sulfur composite dopant, and 1 part of CMC dispersant, add 20 parts of deionized water, and stir in a high-speed stirrer at a speed of 1200 r / min for 40 min to obtain a uniform mixed slurry. S3. Pre-oxidation treatment: Place the mixed slurry in a vacuum drying oven and dry it at 65℃ for 20h; after drying, crush the material in a pulverizer, pass it through a 100-mesh sieve, and place it in a tube furnace. In an oxygen-containing atmosphere with an oxygen volume fraction of 25%, heat it to 250℃ at a heating rate of 4℃ / min and hold it at that temperature for 5h to complete the pre-oxidation. S4. Pre-carbonization treatment: The pre-oxidized material is transferred to a tube furnace in an argon inert atmosphere and heated to 600°C at a heating rate of 6°C / min. The temperature is held for 4 hours to complete the pre-carbonization. S5. Activation and High-Temperature Carbonization: Transfer the pre-carbonized material and continue heating to 900°C at 8°C / min under an argon atmosphere, then introduce the material at a flow rate of 30 mL / min. Gas, heat-activated for 3 hours; after heat-activation, heat up to 1400℃ at the same rate and heat for 7 hours to complete high-temperature carbonization. S6. Pickling and impurity removal: Cool the high-temperature carbonized material to room temperature, soak it in 1.5mol / L dilute hydrochloric acid for 3 hours with continuous stirring at 300r / min to remove residual metal oxides of the composite template agent, then wash it with deionized water until neutral, and dry it at 100℃ for 4 hours.

[0052] S7. Coating and carbonization: The acid-washed and impurity-removed material is mixed evenly with 7% by mass of asphalt, transferred to a tube furnace, and heated to 950℃ at a heating rate of 7℃ / min under an argon atmosphere. The temperature is held for 5 hours. After the holding period, the material is cooled with the furnace and passed through a 325-mesh sieve to obtain the resin-based hard carbon anode material.

[0053] Example 5

[0054] A high-capacity, high-stability resin-based hard carbon anode material is prepared from the following raw materials in parts by weight: 60 parts modified epoxy resin, 5 parts composite pore conditioner, 3 parts nitrogen-phosphorus-sulfur composite dopant, 1 part CMC dispersant, and 20 parts deionized water.

[0055] The modified epoxy resin is prepared by mixing E-51 type epoxy resin and lignin with a molecular weight of 5000 g / mol at a mass ratio of 8:1, adding 2% potassium hydroxide of the total mass, stirring and reacting at 60°C for 2 hours, cooling to room temperature, washing with deionized water until neutral, drying at 80°C for 4 hours, and grinding through a 100-mesh sieve to obtain modified epoxy resin powder. The composite pore regulator is a compound system of MgO-ZnO composite template agent and polystyrene, with a mass ratio of 2:1; the mass ratio of MgO-ZnO is 3:1, and the number average molecular weight of polystyrene is 50000 g / mol.

[0056] The nitrogen-phosphorus-sulfur composite dopant is composed of urea, ammonium dihydrogen phosphate, and thiourea mixed in a mass ratio of 4:2:1.

[0057] The preparation method is as follows: S1. Preparation of modified phenolic resin precursor: Prepare modified phenolic resin powder according to the above method for later use; S2. Preparation of mixed slurry: Mix 60 parts of modified phenolic resin, 5 parts of composite pore conditioner, 3 parts of nitrogen-phosphorus-sulfur composite dopant, and 1 part of CMC dispersant, add 20 parts of deionized water, and stir in a high-speed stirrer at a speed of 1000 r / min for 30 min to obtain a uniform mixed slurry. S3. Pre-oxidation treatment: Place the mixed slurry in a vacuum drying oven and dry it at 60℃ for 12 hours; after drying, crush the material in a pulverizer, pass it through a 100-mesh sieve, and place it in a tube furnace. In an oxygen-containing atmosphere with an oxygen volume fraction of 20%, heat it to 250℃ at a heating rate of 2℃ / min and hold it at that temperature for 3 hours to complete the pre-oxidation. S4. Pre-carbonization treatment: The pre-oxidized material is transferred to a tube furnace in an argon inert atmosphere and heated to 500°C at a heating rate of 3°C / min. The temperature is held for 2 hours to complete the pre-carbonization. S5. Activation and High-Temperature Carbonization: Transfer the pre-carbonized material and continue heating to 800°C at 5°C / min under an argon atmosphere, then introduce the material at a flow rate of 50 mL / min. Gas, heat-activated for 1 hour; after heat-activation, heat up to 1300℃ at the same rate and heat for 6 hours to complete high-temperature carbonization. S6. Pickling to remove impurities: Cool the high-temperature carbonized material to room temperature, soak it in 1mol / L dilute hydrochloric acid for 2 hours with continuous stirring at 200r / min to remove residual metal oxides of the composite template agent, then wash it with deionized water until neutral, and dry it at 80℃ for 4 hours.

[0058] S7. Coating and carbonization: The acid-washed and impurity-removed material is mixed evenly with 5% coal tar pitch by mass, transferred to a tube furnace, and heated to 900℃ at a heating rate of 5℃ / min under an argon atmosphere and held for 3 hours. After the holding period, the carbonized material is cooled with the furnace and passed through a 325-mesh sieve to obtain the resin-based hard carbon anode material.

[0059] Example 6

[0060] A high-capacity, high-stability resin-based hard carbon anode material is prepared from the following raw materials in parts by weight: 80 parts modified epoxy resin, 15 parts composite pore conditioner, 8 parts nitrogen-phosphorus-sulfur composite dopant, 3 parts PVP dispersant, and 40 parts deionized water.

[0061] The modified epoxy resin is prepared as follows: E-51 type epoxy resin and alkali lignin with a molecular weight of 10000 g / mol are mixed at a mass ratio of 10:1, potassium hydroxide accounting for 3% of the total mass is added, the mixture is stirred and reacted at 100℃ for 6 hours, cooled to room temperature, washed with deionized water until neutral, dried at 110℃ for 8 hours, and ground through a 100-mesh sieve to obtain modified epoxy resin powder. The composite pore regulator is a compound system of MgO-ZnO composite template agent and polystyrene, with a mass ratio of 4:1; the mass ratio of MgO-ZnO is 5:1, and the number average molecular weight of polystyrene is 100,000 g / mol.

[0062] The nitrogen-phosphorus-sulfur composite dopant is composed of urea, ammonium dihydrogen phosphate, and thiourea mixed in a mass ratio of 6:3:1.

[0063] The preparation method is as follows: S1. Preparation of modified phenolic resin precursor: Prepare modified phenolic resin powder according to the above method for later use; S2. Preparation of mixed slurry: Mix 80 parts of modified epoxy resin, 15 parts of composite pore conditioner, 8 parts of nitrogen-phosphorus-sulfur composite dopant, and 3 parts of PVP dispersant, add 40 parts of deionized water, and stir in a high-speed stirrer at a speed of 1500 r / min for 60 min to obtain a uniform mixed slurry. S3. Pre-oxidation treatment: Place the mixed slurry in a vacuum drying oven and dry it at 80℃ for 24 hours; after drying, crush the material in a pulverizer, pass it through a 100-mesh sieve, and place it in a tube furnace. In an oxygen-containing atmosphere with an oxygen volume fraction of 30%, heat it to 300℃ at a heating rate of 5℃ / min and hold it at that temperature for 5 hours to complete the pre-oxidation. S4. Pre-carbonization treatment: The pre-oxidized material is transferred to a tube furnace in an argon inert atmosphere and heated to 700°C at a heating rate of 8°C / min. The temperature is held for 4 hours to complete the pre-carbonization. S5. Activation and High-Temperature Carbonization: Transfer the pre-carbonized material and continue heating to 950°C at 8°C / min under an argon atmosphere, then introduce the material at a flow rate of 55 mL / min. Gas, heat-activated for 4 hours; after heat-activated, heat up to 1600℃ at the same rate and heat for 10 hours to complete high-temperature carbonization. S6. Pickling and impurity removal: Cool the high-temperature carbonized material to room temperature, soak it in 2mol / L dilute hydrochloric acid for 4 hours with continuous stirring at 500r / min to remove residual metal oxides of the composite template agent, then wash it with deionized water until neutral, and dry it at 110℃ for 6 hours.

[0064] S7. Coating and carbonization: The acid-washed and impurity-removed material is mixed evenly with 10% coal tar pitch by mass, transferred to a tube furnace, and heated to 1100℃ at a heating rate of 8℃ / min under an argon atmosphere and held for 6 hours. After the holding period, the carbonized material is cooled with the furnace and passed through a 325-mesh sieve to obtain the resin-based hard carbon anode material.

[0065] To further verify the effectiveness of the present invention, the inventors conducted a series of verification experiments, some of which are excerpted below.

[0066] Comparative Example 1 Unlike Example 1, unmodified novolac phenolic resin was used as the precursor, and no composite pore regulator or heteroatom dopant was added. The remaining raw materials and preparation process were completely consistent with Example 1.

[0067] Comparative Example 2 Unlike Example 1, unmodified novolac phenolic resin was used as the precursor, and only a single MgO template agent (80 nm particle size) was added as a pore conditioning agent, with an addition amount of 5 parts. Only urea was added as a nitrogen dopant, with an addition amount of 5 parts. The remaining raw materials and preparation process were completely consistent with Example 1.

[0068] 1. Physical property testing The physical properties of the hard carbon anode materials prepared in Examples 1-4 and Comparative Examples 1-2 were tested, and the test results are shown in Table 1.

[0069] ; It can be seen that the specific surface area of ​​the hard carbon anode material prepared according to the technical solution of the present invention is below 10 m2 / g, the tap density is increased to above 0.8 g / cm3, and the average pore size of the closed pores is below 2.0 nm.

[0070] 2. Electrochemical performance testing The hard carbon anode materials prepared in Examples 1-4 and Comparative Examples 1-2 were mixed with a conductive agent (acetylene black) and a binder (polyvinylidene fluoride, PVDF) at a mass ratio of 82:13:5, respectively. N-methylpyrrolidone (NMP) was added and stirred until homogeneous. The mixture was then coated onto copper foil, dried at 80°C for 12 hours, and rolled (pressure 5-8 MPa) to serve as the anode material. A CR2032 coin cell sodium-ion battery was assembled using a positive electrode, a 1 mol / L NaPF6 / EC-DMC-DEC electrolyte (volume ratio 1:1:1), and a Celgard 2400 separator. Electrochemical performance was tested at room temperature (25℃). The test results are shown in Table 2.

[0071] ; It can be seen that the hard carbon anode material prepared according to the technical solution of the present invention has a reversible specific capacity of up to 403.4 mAh / g, an initial coulombic efficiency of 88.1%, and a capacity retention rate of up to 92.4% after 1000 cycles at a current density of 1 A / g, which is superior to the existing technology.

[0072] This application designs a composite pore regulator that combines a MgO-ZnO composite template agent with a non-carbon-forming polymer to construct a hierarchical pore structure. During carbonization, the MgO-ZnO composite template agent can form a hierarchical pore structure of micropores (<2nm) to mesopores (2-50nm). The micropores provide sufficient sodium storage sites, while the mesopores serve as sodium ion transport channels, accelerating ion diffusion. The polystyrene volatilizes at high temperature, further modifying the pore structure, and at the same time forming a thin carbon layer on the hard carbon surface, reducing the irreversible growth of the SEI film. This solves the defects of low tap density and poor first coulombic efficiency caused by pore formation with a single template agent.

[0073] The preparation method of this invention integrates modification, mixing, carbonization and other steps into one, without the need for complex equipment and harsh process conditions. The raw materials are all industrially available products, and the introduction of lignin further reduces the cost of raw materials. The entire preparation process does not produce any toxic or harmful gases, making it environmentally friendly and solving the problems of complex preparation processes and difficulty in industrialization of existing technologies.

[0074] Although the present invention has been described in detail above with general descriptions, specific embodiments, and experiments, modifications or improvements can be made to it, which will be obvious to those skilled in the art. Therefore, all such modifications or improvements made without departing from the spirit of the present invention fall within the scope of protection claimed by the present invention.

Claims

1. A high-capacity, high-stability resin-based hard carbon anode material, characterized in that, It is prepared from the following raw materials in parts by weight: 60-80 parts of modified resin precursor, 5-15 parts of composite pore regulator, 3-8 parts of heteroatomic dopant, 1-3 parts of dispersant, and 20-40 parts of deionized water; wherein the modified resin precursor is a resin modified by lignin grafting; and the composite pore regulator is a compound system of MgO-ZnO composite template agent and non-carbon-forming polymer.

2. The resin-based hard carbon anode material according to claim 1, characterized in that, The dispersant is polyvinylpyrrolidone or sodium carboxymethyl cellulose; the lignin is alkali lignin; the resin is phenolic resin or epoxy resin; the non-carbon-forming polymer is polystyrene; the mass ratio of the MgO-ZnO composite template agent to polystyrene is 2-4:1; and the heteroatomic dopant is a nitrogen-phosphorus-sulfur composite dopant.

3. The resin-based hard carbon anode material according to claim 2, characterized in that, The particle size of the MgO-ZnO composite template agent is 50-100 nm, the number average molecular weight of the polystyrene is 50,000-100,000 g / mol, the molecular weight of the alkali lignin is 5,000-10,000 g / mol, and the MgO-ZnO composite template agent has a MgO-ZnO mass ratio of 3-5:1; the nitrogen-phosphorus-sulfur composite dopant is composed of urea, ammonium dihydrogen phosphate, and thiourea mixed in a mass ratio of 4-6:2-3:

1.

4. A method for preparing a high-capacity, high-stability resin-based hard carbon anode material, characterized in that, The method is used to prepare the resin-based hard carbon anode material as described in any one of claims 1-3, and includes the following steps: S1. Preparation of modified resin precursor: Mix resin and lignin at a mass ratio of 8-10:1, add 2-3% alkaline catalyst of total mass, stir at 60-100℃ for 2-6h, cool to room temperature after reaction, wash with deionized water until neutral, dry at 80-110℃ for 4-8h, grind through 100 mesh sieve to obtain modified resin precursor; S2. Preparation of mixed slurry: Mix 60-80 parts of modified resin precursor, 5-15 parts of composite channel conditioner, 3-8 parts of heteroatomic dopant, and 1-3 parts of dispersant, add 20-40 parts of deionized water, and stir in a high-speed stirrer at a speed of 1000-1500 r / min for 30-60 min to obtain a uniform mixed slurry. S3. Pre-oxidation treatment: Place the mixed slurry in a vacuum drying oven and dry it at 60-80℃ for 12-24 hours; after drying, crush the material in a pulverizer, pass it through a 100-mesh sieve, and place it in a tube furnace. Under an oxygen-containing atmosphere, heat it to 250-300℃ at a heating rate of 2-5℃ / min and hold it at that temperature for 3-5 hours to complete the pre-oxidation treatment. S4. Pre-carbonization treatment: The pre-oxidized material is transferred to a tube furnace in an argon inert atmosphere and heated to 500-700℃ at a heating rate of 3-8℃ / min, and held for 2-4 hours for pre-carbonization. S5. Activation and High-Temperature Carbonization: Transfer the pre-carbonized material and continue heating it to 800-950℃ at a rate of 5-8℃ / min under an inert argon atmosphere. gas, the At a flow rate of 20-60 mL / min, the temperature is maintained for 1-4 h to activate and regulate the pore structure. After the temperature is maintained, the temperature is raised to 1300-1600℃ at the same rate and maintained for 6-10 h to complete the high-temperature carbonization. S6. Pickling and impurity removal: Cool the high-temperature carbonized material to room temperature, soak it in dilute hydrochloric acid with a concentration of 1-2 mol / L for 2-4 hours, stir continuously at a speed of 200-500 r / min, wash it with deionized water until neutral, and dry it at 80-110℃ for 4-6 hours. S7. Coating and carbonization: The acid-washed and impurity-removed material is mixed evenly with 5-10% by mass of asphalt, transferred to a tube furnace, and heated to 900-1100℃ at a heating rate of 5-8℃ / min under an argon inert atmosphere. The temperature is held for 3-6 hours. After the holding period, the material is cooled with the furnace and passed through a 325-mesh sieve to obtain the resin-based hard carbon anode material.

5. The method for preparing the resin-based hard carbon anode material according to claim 4, characterized in that, In step S3, the oxygen-containing atmosphere is a mixture of oxygen and nitrogen, wherein the oxygen volume fraction is 20-30% and the atmosphere flow rate is 50-80 mL / min.

6. The method for preparing the resin-based hard carbon anode material according to claim 4, characterized in that, In steps S4 and S5, the flow rate of the inert atmosphere is 50-100 mL / min.

7. The method for preparing the resin-based hard carbon anode material according to claim 4, characterized in that, In step S5, The gas flow rate is 30-50 mL / min; in step S6, the dilute hydrochloric acid soaking process is continuously stirred at a stirring rate of 300-500 r / min.

8. The method for preparing the resin-based hard carbon anode material according to claim 4, characterized in that, In step S7, the asphalt is coal tar pitch, which has a softening point of 250±5℃, a coking value of 75-78%, quinoline insolubles of 18-26%, toluene insolubles of 54-58%, and ash content ≤0.3%.

9. An application of a resin-based hard carbon anode material, characterized in that, The resin-based hard carbon anode material is prepared by the method described in any one of claims 1-3. The resin-based hard carbon anode material is used in sodium-ion batteries. The resin-based hard carbon anode material is mixed with a conductive agent and a binder, N-methylpyrrolidone is added, and after stirring evenly, it is coated on copper foil. After drying and rolling, it is used as the anode of sodium-ion batteries and assembled with a positive electrode, electrolyte, and separator to form a sodium-ion battery.

10. The application of the resin-based hard carbon anode material according to claim 9, characterized in that, The conductive agent is acetylene black, and the binder is polyvinylidene fluoride. The resin hard carbon anode material is mixed with acetylene black and polyvinylidene fluoride at a mass ratio of 80-85:10-15:5.